THE SWEAR WORDS USED BY TAIWANESE: A CASE STUDY - Dewi, Feby Febriyanti; Budasi, I Gede (Undiksha Press, 2025)
This study was designed using a descriptive qualitative method that aims to identify swear words and analyze the forms, functions, and references of swear words in the Taiwan language. Primary data in this research was gathered through in-depth interviews, while secondary data was gathered through document analysis. The researcher served as the primary instrument in this study. In addition to the researcher, another instrument was utilized: a questionnaire, which is used to select swear words from document analysis. The next instrument is an interview guide, which is utilized to answer research questions on function and reference. The data were collected from three informants, who are Taiwan tourists visiting Bali. The snowball sampling technique was used as a method of selecting informants. The research found a total of 60 swear words in Taiwanese, classified across various categories. In terms of form, swear words appearas words (23), phrases (27), and clauses (4). For the function of the function swear words, they serve to expressing emotions (24), drawing attention (3), aggression and provocation (36), and have regressive uses (16). Furthermore, the study analyzed the references underlying these swear words, identifying categories such as sex (9), excrement (15), animal names (3), mental illness (18), and personal background (7). These findings answer all research questions set previously allowing for a more in-depth knowledge of the varied nature of swear words in Taiwanese and highlighting the possibility for cross-cultural misunderstandings if not carefully considered.